Serum soluble urokinase plasminogen activator receptor as a potential biomarker of renal impairment severity in diabetic nephropathy. (December 2021) - Lupușoru, Gabriela; Ailincăi, Ioana; Sorohan, Bogdan Marian; Andronesi, Andreea; Achim, Camelia; Micu, Georgia; Caragheorgheopol, Andra; Manda, Dana; Lupușoru, Mircea; Ismail, Gener
Highlights: Serum suPAR level is increased in patients with DKD and DN. suPAR level is correlated with kidney function and proteinuria. suPAR level is correlated with histological lesions of DN. suPAR is associated with severe renal impairment in patients with DN. Abstract: Aims: To investigate serum soluble form of urokinase-type plasminogen activator receptor (suPAR) in patients with diabetic kidney disease (DKD) and biopsy-proven diabetic nephropathy (DN), its correlation with histological parameters and its capacity as a biomarker for renal impairment severity. Methods: We conducted a cross-sectional study on 75 patients with diabetes mellitus (DM) and DKD, among whom 28 had biopsy-proven DN. Results: Among the 75 patients, 9 (12%) had type 1 and 66 (88%) type 2 DM. The median value of the serum suPAR level was 2857.2 pg/mL (1916.4–3700) in the entire cohort and 2472.1 pg/mL (1782.6–3745.8) in the biopsy-proven DN subgroup, respectively. suPAR was significantly correlated with diabetes duration, diabetic retinopathy, anti-proteinuric treatment, albuminuria, kidney function, DN class, interstitial fibrosis and tubular atrophy (IFTA) score and with interstitial inflammation score. suPAR had a good accuracy for the association with chronic kidney disease (CKD) stages G3b-5, macroalbuminuria, DN class IV, IFTA score 3 and interstitial inflammation score 2. Conclusions: Serum suPAR was increased in DN patients and was associated with DM duration, diabetic retinopathy, renoprotective treatment, kidney function, proteinuria, DN class, IFTA and interstitial inflammation scores. Also, suPAR had a good capacity as a biomarker for advanced renal impairment and severe histological lesions of DN.